Effect of land configuration and weed management on productivity of greengram (Vigna radiata) - Singh, Guriqbal; Virk, Harpreet Kaur; Khanna, Veena (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted to study the effect of different land configuration and weed management treatments in greengram (Vigna radiata L.). The raised bed and ridge sown crop recorded significantly lower dry matter of weeds and significantly higher weed control efficiency (WCE) (78.4% and 78.1%, respectively ) than flat sown crop (68.5%). Raised bed sowing provided higher grain yield to the tune of 4.0 and 16.1% over ridge and flat sowing, respectively and gave significantly higher gross returns, net returns and B:C ratio than ridge and flat sowings. Application of pendimethalin @ 0.75 kg/ha as pre-emergence (PE) + imazethapyr @ 55 g/ha as post-emergence (POE) 15-20 days after sowing (DAS) and imazethapyr @ 55 g/ha (POE) 15-20 DAS recorded significantly lower dry matter of weeds and significantly higher WCE than pendimethalin @ 0.75 kg/ha (PE). The application of herbicides (pendimethalin as PE and imazethapyr as POE) had no adverse affect on symbiotic parameters. Pendimethalin @ 0.75 kg/ha (PE) + imazethapyr @ 55 g/ha 15-20 DAS provided significantly higher grain yield than the other treatments and gave the highest gross returns, net returns and B:C ratio. It can be concluded that sowing of greengram on raised bed land configuration along with application of pendimethalin @ 0.75 kg/ha (PE) + imazethapyr @ 55 g/ha 15-20 DAS was found to be effective for controlling weeds as well as improving the grain yield and providing higher net returns and B:C ratio.